(untitled) (Research, Society and Development, 2024)
This is a quantitative, documentary, descriptive cross-sectional study, in which the cervicovaginal cytology exams of the Municipal Laboratory of Caruaru-PE, carried out between October and December 2022, were evaluated. The aim of the study was to determine the frequency of representation of the transformation zone/JEC and lesions in the cervicovaginal cytopathology exams of women seen in the municipality of Caruaru-PE. During the analysis, the following variables were observed: age, inspection of the cervix, epithelia represented in the sample and presence or absence of lesions. The data was stored on the Google Forms platform and transformed into graphs using Excel 2016. A total of 3,953 samples were evaluated, but 1,170 were unsatisfactory for cytological examination. Of the 2,783 tests included for research, only 1,590 showed a representation of the Transformation Zone/JEC and 152 showed some kind of lesion. Of these 152 women who had a lesion, 131 had a representation of the Transformation Zone/JEC in the test, corroborating the literature, which shows how important the presence of a representation of the Transformation Zone/JEC in cervicovaginal cytology samples is for a diagnosis of a lesion. In view of the results obtained in this study, the importance of all the phases of the cytopathological examination can be seen. It has been shown that collection has a direct impact on the sensitivity and interpretation of the examination, which requires training for health professionals on cervical cancer screening in basic health units, which should be periodic due to the high turnover of professionals within the SUS.